Development and implementation of intranasal naloxone opioid overdose response protocol at a homeless health clinic. Issue 1 (26th March 2015) - Dahlem, Chin Hwa Y.; Horstman, Molly J.; Williams, Brent C.
Abstract: Purpose: To describe the development, implementation, and preliminary evaluation of Opioid Overdose Response Protocol using intranasal (IN) naloxone in a homeless shelter. Data sources: Opioid Overdose Response Protocol and training curriculum were developed using the Massachusetts Department of Public Health Opioid Overdose Education and Naloxone Distribution (OEND) flow chart, the American Heart Association (AHA) simplified adult basic life support algorithm, and resources through Harms Reduction Coalition. Conclusions: Intranasal naloxone offers a safe and effective method for opioid reversal. To combat the rising incidence of opioid overdose, IN naloxone should be made available at homeless shelters and other facilities with high frequency of opioid overdose, including the training of appropriate staff. This project has demonstrated the effective training and implementation of an Opioid Overdose Response Protocol, based on feedback received from cardiopulmonary resuscitation (CPR) trained nonhealthcare staff. Nurse practitioners (NPs), with our focus on patient care, prevention, and education, are well suited to the deployment of this life‐saving protocol. Implications for practice: NPs are in critical positions to integrate opioid overdose prevention education and provide naloxone rescue kits in clinical practices.